On the Origin of Neutrophil Extracellular Traps in COVID-19 - Pastorek, Michal; Dúbrava, Martin; Celec, Peter (Frontiers in Immunology, 2022)
Despite ongoing vaccination COVID-19 is a global healthcare problem because of the lack of an effective targeted therapy. In severe COVID-19 manifesting as acute respiratory distress syndrome, uncontrolled innate immune system activation results in cytokine deregulation, damage-associated molecular patterns release upon tissue damage and high occurrence of thrombotic events. These pathomechanisms are linked to neutrophil function and dysfunction, particularly increased formation of neutrophil extracellular traps (NETs). While the association of NETs and severity of COVID-19 has been shown and proved, the causes of NETs formation are unclear. The aim of this review is to summarize potential inducers of NETs formation in severe COVID-19 and to discuss potential treatment options targeting NETs formation of removal.